Boat engine maintenance training for Rezki Mahakam Baru fishermen group, Samarinda City - Mika Patayang; Herdi Syam; Wahyudianto Wahyudianto (Universitas Muhammadiyah Magelang, 2022)
Catching fish, both small and large scale must be supported by the feasibility of the ship and good fishing equipment so that the results obtained are also maximized. RT 32, Rawa Makmur Village, Palaran District, Samarinda City has several fishermen groups, one of which is the Rezki Mahakam Baru fishermen group consisting of 15 people. One of the obstacles faced by the community in operating their ships is damage to the ship's engine due to lack of maintenance. Therefore, this community service is carried out with the aim of increasing the ability of fishermen to maintain ship engines. The activity was carried out by providing training on single cylinder ship engine maintenance. The results of this activity indicate an increase in the knowledge and understanding of fishermen in overcoming ship engine damage.